2016
DOI: 10.1371/journal.pone.0148394
|View full text |Cite
|
Sign up to set email alerts
|

Change in Obesity Prevalence across the United States Is Influenced by Recreational and Healthcare Contexts, Food Environments, and Hispanic Populations

Abstract: ObjectiveTo examine change in county-level adult obesity prevalence between 2004 and 2009 and identify associated community characteristics.MethodsChange in county-level adult (≥20 years) obesity prevalence was calculated for a 5-year period (2004–2009). Community measures of economic, healthcare, recreational, food environment, population structure, and education contexts were also calculated. Regression analysis was used to assess community characteristics associated (p<0.01) with change in adult obesity pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 31 publications
(54 reference statements)
4
36
0
2
Order By: Relevance
“…Given the current obesity crisis Ogden Carroll, Lawman, Fryar, Kruszon-Moran, Kit, & Flegal, 2016), it has become increasing clear that certain environmental constraints raise the risks for obesity (Myers, Slack, Martin, Broyles, & Heymsfield, 2016), and that there is a remarkable amount of nutritional misinformation circulating in popular culture (Korownyk, Kolber, McCormack, Lam, Overbo, Cotton, & Allan, 2014;Wansink, 2005). Nutritional knowledge has thus become essential for maintaining a healthy lifestyle.…”
Section: Post-secondary Nutrition Science Educationmentioning
confidence: 99%
“…Given the current obesity crisis Ogden Carroll, Lawman, Fryar, Kruszon-Moran, Kit, & Flegal, 2016), it has become increasing clear that certain environmental constraints raise the risks for obesity (Myers, Slack, Martin, Broyles, & Heymsfield, 2016), and that there is a remarkable amount of nutritional misinformation circulating in popular culture (Korownyk, Kolber, McCormack, Lam, Overbo, Cotton, & Allan, 2014;Wansink, 2005). Nutritional knowledge has thus become essential for maintaining a healthy lifestyle.…”
Section: Post-secondary Nutrition Science Educationmentioning
confidence: 99%
“…26 In such a skewed food environment, nutrition education is most likely insufficient to improve the population's eating habits. 27,28 To start curbing the rise in the prevalence of obesity, changes in the food environment are essential to make the healthy choice the easy choice.…”
Section: Introductionmentioning
confidence: 99%
“…For hospital stays, we ran sensitivity analyses using OLS models and found that the model fit was better with Poisson regression. In all models, we also included a state‐level fixed effect to adjust for unobserved state‐level differences, an approach that has been used in other county‐level health research to reduce bias introduced by differences in state policies and environments . For preventable hospitalizations, smaller coefficients indicate better outcomes; the reverse is true for HbA1c monitoring and mammography screening.…”
Section: Methodsmentioning
confidence: 99%